Clinical and Etiological Characteristics of Atypical Hand-Foot-and-Mouth Disease in Children from Chongqing, China: A Retrospective Study. (26th November 2015) - Yan, Xiang; Zhang, Zhen-Zhen; Yang, Zhen-Hua; Zhu, Chao-Min; Hu, Yun-Ge; Liu, Quan-Bo
Abstract : Background . Hand-foot-and-mouth disease (HFMD) is a disease that had similar manifestations to chickenpox, impetigo, and measles, which is easy to misdiagnose and subsequently causes delayed therapy and subsequent epidemic. To date, no study has been conducted to report the clinical and epidemiological characteristics of atypical HFMD. Methods . 64 children with atypical HFMD out of 887 HFMD children were recruited, stool was collected, and viral VP1 was detected. Results . The atypical HFMD accounted for 7.2% of total HFMD in the same period (64/887) and there were two peaks in its prevalence in nonepidemic seasons. Ten children (15.6%) had manifestations of neurologic involvement, of whom 4 (6.3%) were diagnosed with severe HFMD and 1 with critically severe HFMD, but all recovered smoothly. Onychomadesis and desquamation were found in 14 patients (21.9%) and 15 patients (23.4%), respectively. The most common pathogen was coxsackievirus A6 (CV-A6) which accounted for 67.2%, followed by nontypable enterovirus (26.6%), enterovirus 71 (EV-A71) (4.7%), and coxsackievirus A16 (A16) (1.5%). Conclusions . Atypical HFMD has seasonal prevalence. The manifestations of neurologic involvement in atypical HFMD are mild and usually have a good prognosis. CV-A6 is a major pathogen causing atypical HFMD, but not a major pathogen in Chongqing, China.